Detection of antibacterial activity in chicken meat, eggs, drinking water, animal feed and sewage waste in Tabanan, Bali - Setiabudy, Marta; Indraningrat, Anak Agung Gede; Suryanditha, Putu Arya; Budayanti, Ni Nyoman Sri; Yanti, Ni Komang Semara; Adhiputra, I Ketut Agus Indra; Widowati, I Gusti Ayu Rai; Agustina, Kadek Karang (Indonesian Society for Clinical Microbiology (Perhimpunan Dokter Spesialis Mikrobiologi Klinik Indonesia), 2023)
Background: The use of antibiotics that are not in accordance with the indications, doses, and duration can trigger resistance and there is concern that it might leave antibiotic residues in the processed product. Aim of this study was to detect the antibacterial activity of livestock products, namely chicken meat and eggs and the surrounding environment such as drinking water, animal feed and waste disposal. This study was a preliminary study before the establishment of antibiotic wise village, One Health approach for antimicrobial stewardship program. Methods: This study was a descriptive study with a cross sectional design to determine antibacterial activity, particularly tetracycline in livestock products and the environment. The research samples were taken from 5 groups of farmers in one of the villages in Tabanan, Bali. Bioassay method based on the Kirby Bauer method was used in this study. Results: From a total of 44 samples, 6 samples showed weak antibiotic tetracycline activity (13.6%), namely in waste disposal (20%) and animal feed (40%). Antibiotic contamination was likely to occur because the animal feed used in this group contains antibiotics with or without the knowledge of the farmers themselves. Disposal waste came from livestock manure that ate the feed or from animal feed that was scattered around the cage. Conclusion: Samples of livestock meat and eggs did not show antibacterial activity. There were samples that have antibiotic activity but weak and inconsistent, namely in samples of waste disposal and animal feed. This condition cannot necessarily be concluded as antibiotic abuse in livestock however it can be the basis for the importance of providing education regarding antimicrobial resistance. Unless there was indication, antibiotics should not be given to livestock on a daily basis.